CityScapeLab Berlin: A Research Platform for Untangling Urbanization Effects on Biodiversity. - Lippe, Moritz von der; Buchholz, Sascha; Hiller, Anne; Seitz, Birgit; Kowarik, Ingo (MDPI, 2020)
Urban biodiversity conservation requires an understanding of how urbanization modulates biodiversity patterns and the associated ecosystem services. While important advances have been made in the conceptual development of urban biodiversity research over the last decades, challenges remain in understanding the interactions between different groups of taxa and the spatiotemporal complexity of urbanization processes. The CityScapeLab Berlin is a novel experimental research platform that allows the testing of theories on how urbanization affects biodiversity patterns and biotic interactions in general and the responses of species of conservation interest in particular. As the backbone of the research platform dry grassland patches are choosen because they are common in many urban regions, extend over a wide urbanization gradient, and usually harbor diverse and self-assembled communities. Focusing on a standardized type of model ecosystem allowed the urbanization effects on biodiversity to be unraveled from effects that would otherwise be masked by habitat- and land-use effects. The CityScapeLab combines different types of spatiotemporal data on (i) various groups of taxa from different trophic levels, (ii) environmental parameters on different spatial scales, and (iii) on land-use history. This allows for the unraveling of the effects of current and historical urban conditions on urban biodiversity patterns and the related ecological functions
Keywords: Urbanisierung; Wirkungsanalyse; Biodiversität; Stadtökologie; Grünfläche; Langzeitmonitoring; Sozioökonomischer Wandel; Raumveränderung